Faktor-Faktor yang Memengaruhi Perilaku Komunikasi Penyuluhan Pertanian - Wardhani, Andy Corry (Mediator, 2006)
This research aimed to gain a clear description over some factors which influenced communication process conducted by agricultural facilitators—both partially, and simultaneously. Employing explanatory method of research, a sample of 116 agricultural facilitators from Kabupaten Indramayu, Kabupaten Bandung, and Kabupaten Tasikmalaya was chosen using stratified random sampling. Data was generated from questionnaire and a series of selected interviews. It is found that personal and situational factors affected facilitators communication act in the three regions. Compared with situational factors, personal factors have stronger effect.